Pengenalan Flashcard sebagai Media untuk Meningkatkan Kemampuan Bahasa Inggris - Sisca Wulansari Saputri (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
Learning abilities so that they can stimulate or encourage the learning process to be more interesting. flashcard is a media that helps in remembering and reviewing learning materials such as: definitions or terms, symbols, spelling of foreign languages, formulas, and others. The purpose of this Community Service activity is to introduce the use of Flashcards in learning English specifically to improve the understanding of the English vocabulary of students and students at SATAP SMPN 2 Kepuh, Kec. Pincincang. Community service activities by providing socialization of the application of flashcard media in learning English in order to improve the students' cognitive abilities and stimulate students to think creatively have been carried out properly. With good cooperation between the implementation team and partners, this community service activity will run as expected. With this service, teachers are expected to be able to implement flashcard media in English, as well as students can understand so that they can improve their cognitive abilities in learning English.